Penambahan Pupuk Organik Cair Dari Ampas Kopi Sebagai Nutrisi Pada Sistem Hidroponik terhadap Pertumbuhan Tanaman Selada (Lactuca sativa L) - Putra, Ridho Agusliandi; Sembiring, Ayu Kinanti; Anggraini, Dian Elsi; Sitanggang, Lucia Berdo; Amar, M Rizky; Sihombing, Priskila Rotalenta; Susilawati, Susilawati (Seminar Nasional Lahan Suboptimal, 2021)
Putra RA, Sembiring AK, Anggraini DE, Sitanggang LB, Amar MR, Sihombing PR, Susilawati S. 2021. Addition of liquid organic fertilizer from coffee grounds as nutrients in a hydroponic system on the growth of lettuce (Lactuca sativa L). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimalke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 891-899.Â  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Â Hydroponics is a way of growing without using soil media which generally uses AB mix nutrients as inorganic fertilizer for plants. In order to reduce the use of sustainable hydroponic basic nutrients, an alternative nutrient source is added in the form ofPOC (Liquid Organic Fertilizer). One of the ingredients used in making POC is coffee grounds. The purpose of this study was to identify the potential of Liquid Organic Fertilizer (POC) from coffee grounds as a nutrient enhancer in a hydroponic system for the growth of lettuce (Lactuca sativa L.). It is suspected that the use of POC coffee grounds contains nitrogen and phosphorus which can help your plants grow faster and fertile. This study used coffee grounds fermentation which was used as POC according to the composition contained in the literature journal as a nutritional enhancer on lettuce growth, as well as the effect given by the POC. Coffee grounds contained 2.28% nitrogen, 0.06% phosphorus and 0.6 potassium. The pH of coffee grounds was slightly acidic, around 6.2 on the pH scale. In addition, coffee grounds also contained magnesium, sulfur, and calcium which were useful for plant growth. The treatment of liquid organic fertilizer (POC) from coffee grounds had an effect on the growth of lettuce plants on all variables, namely the number of leaves (strands), leaf length (cm), leaf width (cm), plant height (cm), and root length (cm). Giving POC with the same concentration in each plant gave significant results in plant height. From the results of the study, it can be concluded that coffee grounds can be used as a nutrient enhancer for the growth of lettuce (Lactuca sativa) with hydroponic media.